Multifarious Impact of Rhodanine Acceptor Group on the Optical Properties of Some Semiconductor Probes. Issue 11 (5th October 2021) - Ghosh, Tapan; Mondal, Madalasa; Vijayaraghavan, Ratheesh K.
Abstract: Steady state optical properties such as photo‐absorption and photo‐luminescence characteristics of organic molecules in its bulk states viz, film or crystalline forms are highly sensitive to subtle alteration of chemical substitution, molecular geometry in bulk and the electronic state coupling between a pair of molecules. Here we highlight a distinct interference of rhodanine substitution on such optical properties of a group of similar molecules (2TR, 23TR ). For comparison an anthracene conjugate model molecule was also chosen (AR ). In the former case, despite of having similar molecular structure except the presence of a methyl group at the C3 position (which ensures the identical electronic states in both the case) and similar molecular packing in single crystals, 2TR and 23TR exhibited diagonally opposite solid‐state fluorescence behavior. 2TR was non‐fluorescent whereas, 23TR was highly emissive in its crystalline solid state. A minute substitutional change in chemical structure was found to alter the solid‐state fluorescence behavior immensely that was attributed to the non‐radiative loss in the former case due to the solid‐state C−C bond flip which was further proven by temperature dependent fluorescence experiments. At a sample temperature of <120 K, 20‐fold enhancement in the fluorescence intensity was observed. Abstract : Photophysical properties of small molecular semiconductors are found to be sensitive to a minor substitution of methyl group to the thiophene ring. Optical and solid state packing features correlating these two aspects have been summarized in the manuscript with a model compound as well.